Decoding lung complexity: single-cell sequencing in lung diseases, regeneration, and drug discovery - Wang, Peng; Tang, Nan (Frontiers in Drug Discovery, 2024)
The lung is constantly exposed to the external environment, making it highly susceptible to infections and injuries caused by airborne pollutants and pathogens. Understanding the cellular players and molecular mechanisms underlying post-injury lung repair is essential for elucidating the repair processes following injury. Single-Cell Sequencing (sc-seq) offers unprecedented single-cell resolution, enabling researchers to dissect the complex biological profiles that drive diverse lung pathologies and to uncover the signaling pathways crucial for lung regeneration. This review will explore the latest findings in lung diseases and regeneration revealed by sc-seq. Additionally, we will highlight how continuous advancements in sc-seq technology are paving the way for the development of novel drugs aimed at targeting pathways involved in lung regeneration and treating lung diseases. By offering single-cell resolution, recent advancements in sc-seq have enabled researchers to dissect multiple layers of biological profiles underlying diverse lung pathogenesis and uncover signaling pathways critical for lung regeneration. In this review, we will discuss recent sc-seq findings in lung diseases and regeneration. Continuous advancements in sc-seq technology hold great promise for facilitating the development of novel drugs targeting lung regeneration pathways and lung diseases. These repair processes are mediated by resident epithelial stem cells and their niche cells.